The bimodal rise and fall acute coronary syndromes curves paralleling COVID-19 outbreaks. (14th October 2021) - Trabattoni, D; Teruzzi, G; Ravagnani, P M; Santagostino Baldi, G; Montorsi, P; Calligaris, G; Galli, S; Bartorelli, A L
Abstract: Introduction: Preliminary reports from the early phase of COVID-19 epidemic in Italy reported a dramatic reduction in hospital admission rates for acute coronary syndromes (ACS) coupled with longer times from symptoms onset to hospital presentation. Purpose: To assess the impact of COVID-19 on hospital admission rates and ACS patterns, as well as time to presentation and clinical outcomes, following the acute pandemic phase in 2020 compared to previous year. Methods: We conducted a single institution retrospective analysis conducted in a cardiovascular hub serving a large metropolitan area in Italy. Number and monthly distribution of hospital admissions for ACS from January 1 to December 31, 2020 were compared to the respective figures in 2019. Baseline clinical features, time from symptoms onset to hospital admission and main clinical outcomes were collected. Results: A total of 599 ACS cases were recorded in 2020 vs. 386 cases in 2019, with a net 55% increase. ACS presentation rate in 2020 showed a bimodal pattern, paralleling the most contagious outbreak periods (Figure 1). SARS-CoB-2 nasopharyngeal swab or specific antibody tests were positive in 34 (5.7%) patients. Time from symptoms onset to hospital presentation tended to be longer in 2020 than in 2019, being two-fold longer during the peak epidemic phase (February 21-May 3, 2020; median time 2.0 vs. 5.0 hours, p=0.030). The proportion of late-presenting STEMI (>8 hrs from symptoms onset) was higher in 2020 compared to 2019 (30% vs. 18%, p=0.003), as well as higher was in-hospital mortality (15% in 2020 vs 6% in 2019, p=0.001), partly due to a three-fold increase in cardiogenic shock on ACS presentation. Conclusions: ACS admission rate significantly increased during the 2020 COVID-19 epidemic outbreak for several reasons only partially explained by a SARS-CoV-2 infection trigger effect on ACS. Longer presentation times and higher rates of cardiogenic shock and mortality were observed, urging the need health-care systems to keep a high priority on cardiovascular emergencies response networks. FUNDunding Acknowledgement: Type of funding sources: None.